Análise da relação entre desenvolvimento e índice de qualidade do ar: uma análise municipal - Santos, João Vitor Acca dos (Universidade Federal de São Carlos, 2024)
Economic development is a phenomenon that, given certain circumstances, can be linked to the exploitation and degradation of the environment. Therefore, encouraging sustainable economic development is of great importance. In this sense, the best-known theory that relates economic development and environmental degradation is the Environmental Kuznets Curve (CAK). CAK is a theoretical concept that postulates a relationship between environmental degradation and the process of economic development through a curve in the shape of an inverted “U”. One of the main environmental impacts caused by development is atmospheric pollution, with the deterioration of air quality, causing environmental problems and health problems. In order to control air pollution and its risks, several countries establish air quality parameters, through which they are able to assess its condition and implement measures to maintain it. Thus, the study sought, through a panel data model, to identify the relationship between the air quality index and pollution during the period from 2015 to 2020 in 6 states in Brazil. This work aims to analyze air quality, measured by the air quality index using the annual pollutant concentration (PM10), for the states of São Paulo, Rio de Janeiro, Ceará, Rio Grande do Sul, Pernambuco and Minas Gerais and relating it to several variables that represent the level of economic development, such as GDP per capita, population and industrial GDP, will finally verify the possibility of finding a curve similar to CAK.
Analysis of the relationship between development and quality index: a municipal analysis
Keywords: Poluição; CAK; Desenvolvimento; desenvolvimento sustentável; Pollution; CAK; Development; Sustainable development; CIENCIAS SOCIAIS APLICADAS::ECONOMIA